Protocol for the feasibility and implementation study of a model of best practice in primary care led postdiagnostic dementia care: PriDem - Rachael Hunter; Natalia Lago; Louise Robinson; Greta Rait; Kate R Walters; Marie Poole; Claire Bamford; Jill Manthorpe; Jane Wilcock; Karen Harrison Dening; Martin Knapp; Sube Banerjee; et al. (BMJ Open)
Introduction Care is often inadequate and poorly integrated after a dementia diagnosis. Research and policy highlight the unaffordability and unsustainability of specialist-led support, and instead suggest a task-shared model, led by primary care. This study is part of the PriDem primary care led postdiagnostic dementia care research programme and will assess delivery of an evidence-informed, primary care based, person-centred intervention. The intervention involves Clinical Dementia Leads (CDLs) working in primary care to develop effective dementia care systems that build workforce capacity and support teams to deliver tailored support to people living with dementia and their carers.Methods and analysis This is a 15-month mixed-methods feasibility and implementation study, situated in four National Health Service (NHS) primary care networks in England. The primary outcome is adoption of personalised care planning by participating general practices, assessed through a patient records audit. Feasibility outcomes include recruitment and retention; appropriateness and acceptability of outcome measures; acceptability, feasibility and fidelity of intervention components. People living with dementia (n=80) and carers (n=66) will be recruited through participating general practices and will complete standardised measures of health and well-being. Participant service use data will be extracted from electronic medical records. A process evaluation will explore implementation barriers and facilitators through methods including semistructured interviews with people living with dementia, carers and professionals; observation of CDL engagement with practice staff; and a practice fidelity log. Process evaluation data will be analysed qualitatively using codebook thematic analysis, and quantitatively using descriptive statistics. Economic analysis will determine intervention cost-effectiveness.Ethics and dissemination The study has received favourable ethical opinion from Wales REC4. NHS Confidentiality Advisory Group support allows researchers preconsent access to patient data. Results will inform intervention adaptations and a future large-scale evaluation. Dissemination through peer-review journals, engagement with policy-makers and conferences will inform recommendations for dementia services commissioning.Trial registration number ISRCTN11677384.